ASEM VI: la renovación del proceso - Abad, Gracia (UNISCI Discussion Papers, 2007)
The 6th ASEM summit, held a decade after the beginning of the process which gives it its name, constituted a unique opportunity to make an assessment of its achievements as well as to establish new principles to allow the process to go forward. According to the article, three aspects may be considered as the main results of the summit: the adoption of global challenges as the main focus of the Asia-Europe dialogue, the improvement of the working methods and the second enlargement.